Automated Large‐Scale Full Seismic Waveform Inversion for North America and the North Atlantic. Issue 7 (28th July 2018) - Krischer, Lion; Fichtner, Andreas; Boehm, Christian; Igel, Heiner
Abstract: We present a new anisotropic seismic tomography model based on a multiscale full seismic waveform inversion for crustal and upper‐mantle structure from the western edge of North America across the North Atlantic and into Europe. The gradient‐based inversion strategy utilizes the adjoint state method coupled with an L‐BFGS quasi‐Newton optimization scheme. To improve the handling of large data quantities in the context of full seismic waveform inversions, we developed a workflow framework automating the procedure across all stages, enabling us to confidently invert for waveforms from 72 events recorded at 7, 737 unique stations, resulting in a total of 144, 693 raypaths, most of them with three‐component recordings. The final model after 20 iterations is able to explain complete waveforms including body as well as surface waves of earthquakes that were not used in the inversion down to periods of around 30 s. The model is complemented by a detailed resolution analysis in the form of 3‐D distributions of direction‐dependent resolution lengths. Key Points: We performed a multiscale, radially anisotropic waveform inversion at periods from 30 to 120 s A fully automated inversion procedure enables the incorporation of large‐scale data sets The 20 L‐BFGS iterations result in a model that explains complete waveforms